Optimal intervals for follow-up cystoscopy in non-muscle invasive bladder cancer: a systematic review regarding oncological safety. (2nd January 2022) - Dreyer, Thomas; Ernst, Andreas; Jensen, Jørgen Bjerggaard
Abstract: Context: Improving efficiency of follow-up for non-muscle invasive bladder tumours (NMIBC) without risking disease progression through delays of recurrence diagnosis, is a highly relevant field of research. Objective: The aim of our systematic review was to investigate whether the available evidence support alternative follow-up cytoscopic schedules with respect to oncological safety, compared to those currently given in clinical guidelines for NMIBC. Evidence acquisition we included prospective studies investigating cystoscopy based follow-up schedules including, but not restricted to, comparison of two or more different follow-up schedules with respect to oncological safety measured by recurrence free survival, progression free survival, and overall survival. We allowed for supplementation of modalities such as urinary biomarkers. We screened 680 studies identified by a systematic literature search and, based on our inclusion and exclusion criteria, we included three studies for the narrative synthesis of evidence. Conclusion: In our systematic search of the literature, we found only low level evidence to support current or alternative cystoscopic follow-up schedules. Clinical trials directly aimed at investigating novel follow-up schedules for NMIBC are needed before substantial changes to existing clinical guidelines can be made.